Antara Pembangunan Ekonomi dan Degradasi Lingkungan - M. Firmansyah; Diah Setyorini Gunawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
This paper describes the linkage between economic development and environmental degradation, while economics growth being the center of national economic development indicators. The degradation of natural resources is not the unique attribute of advanced Western industrial economic. But, it happens on Eastern economics bloc and the low growth economics countries also. The searching of win-win solution is tried by economic agents – government, entrepreneur, and societies, to create the balancing decision that stimulate all advantages on development policy application.Keywords: economic growth, environmental degradation, economic agents